Стратегії та механізм забезпечення економічної безпеки зовнішньоекономічної діяльності підприємств - Прокопенко, О. В.; Школа, В. Ю.; Домашенко, М. Д. (Видавництво Львівської політехніки, 2015)
Висвітлено особливості формування системи управління економічною безпекою зовнішньоекономічної діяльності підприємств, яка охоплює стратегії та механізм управління економічною безпекою зовнішньоекономічної діяльності підприємств, рекомендовано під механізмом забезпечення економічної безпеки ЗЕД машинобудівного підприємства розуміти складову системи управління підприємством, яка на основі вибраної органами управління цілі щодо підтримки або підвищення рівня економічної безпеки ЗЕД з використанням наявного потенціалу підприємства забезпечує реалізацію поставленої мети та приводить до стабільної та ефективної роботи підприємства, запропоновано трикомпонентний показник оцінки рівня економічної безпеки підприємства, який охоплює: оцінку потенціалу підприємства для здійснення ЗЕД; рівень країнового ризику країни; показник рівня ринкових можливостей підприємства. The article deals with peculiarities of forming foreign economic activities economic security management system at enterprises, including strategies and mechanisms of foreign economic activities economic security control. Foreign economic activities economic security management at the enterprise includes organizational and economic control mechanism structure, functions, managerial decisions, which together lead to fulfillment of the main task, it being provision of efficient and smooth enterprise operation. Functioning of organizational and economic mechanism of controlling foreign economic activities economic security should be considered as the activity oriented to achieving managerial goals, and the state of this mechanism should be taken as the criterion to determine the foreign economic activities economic security level. However, to determine managerial aims achievement degree is a complex task, which requires detailed lead-up to choose factors influencing the general level of the enterprise foreign economic activities economic security. These factors should comprehensively determine the enterprise foreign economic activities economic security level, to characterize enterprise activities, its short-term and long-term results both inside and outside the enterprise. Foreign economic activities economic security providing mechanism of the machine building enterprise is an enterprise control system constituent, which on the basis of the aim chosen by authorities concerning foreign economic activities economic security level maintaining or increasing through using the enterprise potential, provides the stated aim realization and leads to enterprise stable and effective work. Organizational and economic mechanism to control foreign economic activities economic security at the enterprise is multilevel, therefore it is possible to achieve the set goals only when all systems and mechanism constituents are mutually coordinated. Applying this mechanism allows to create new scheme of cooperation between enterprise control system elements and to make the foreign economic activities economic security control more effective, logic and systematic. Strategies to provide enterprise economic security are constituents of the mechanism. They are chosen depending on the economic security zone, corresponding to each analyzed foreign economic activities directions. The three-component factor to estimate the enterprise economic security level is suggested to consider internal and external factors, which influence the enterprise economic security during its entering the foreign market. It includes evaluation of the enterprise foreign economic activities potential; level of the country risk; factor of the enterprise market abilities level. Development of the approach to forming strategies and the mechanism to provide foreign economic activities economic security at the enterprise will allow to increase the economic security general level, to stimulate administrative staff to take measures oriented towards efficient use of enterprise resources, to choose the optimal market for selling its products, and to choose the activities that will satisfy the international market needs.
Strategies and mechanisms to provide economic security of enterprise foreign economic activities
Keywords: економічна безпека; механізм управління; зовнішньоекономічна діяльність (ЗЕД); стратегії; заходи; оцінка рівня; economic security; control mechanism; foreign economic activities; strategies; measures; evaluation of level